DEVELOPMENT OF ROAD INFRASTRUCTURE TO IMPROVE TRAFFIC SMOOTHNESS IN WEST PAPUA - Nico Djundharto Djajasinga (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
Development has a function to improve the welfare of the surrounding community. Therefore, West Papua Province then carried out development to support the daily activities of the local community so that their activities could run well. This study aims to see how the development of road infrastructure will function to increase the smoothness of traffic in the province of West Papua. This research will be carried out using a qualitative approach. The data used were obtained from various research results and previous studies. The results of this study found a positive effect that comes from the development of this infrastructure in the form of helping the community’s daily activities and activities. However, several negative effects come from this development, namely the obligation for the government to carry out compensation for various properties belonging to local residents who must be sacrificed for the development of this infrastructure.